EuPaGDT: a web tool tailored to design CRISPR guide RNAs for eukaryotic pathogens. Issue 4 (30th October 2015) - Peng, Duo; Tarleton, Rick
Abstract : Recent development of CRISPR-Cas9 genome editing has enabled highly efficient and versatile manipulation of a variety of organisms and adaptation of the CRISPR-Cas9 system to eukaryotic pathogens has opened new avenues for studying these otherwise hard to manipulate organisms. Here we describe a webtool, Eukaryotic Pathogen gRNA Design Tool (EuPaGDT; available athttp://grna.ctegd.uga.edu ), which identifies guide RNA (gRNA) in input gene(s) to guide users in arriving at well-informed and appropriate gRNA design for many eukaryotic pathogens. Flexibility in gRNA design, accommodating unique eukaryotic pathogen (gene and genome) attributes and high-throughput gRNA design are the main features that distinguish EuPaGDT from other gRNA design tools. In addition to employing an array of known principles to score and rank gRNAs, EuPaGDT implements an effective on-target search algorithm to identify gRNA targeting multi-gene families, which are highly represented in these pathogens and play important roles in host–pathogen interactions. EuPaGDT also identifies and scores microhomology sequences flanking each gRNA targeted cut-site; these sites are often essential for the microhomology-mediated end joining process used for double-stranded break repair in these organisms. EuPaGDT also assists users in designing single-stranded oligonucleotides for homology directed repair. In batch processing mode, EuPaGDT is able to process genome-scale sequences, enabling preparation of gRNA libraries for large-scale screening projects.